INBRX-106: a hexavalent OX40 agonist that drives superior antitumor responses via optimized receptor clustering - William L Redmond; Yoshinobu Koguchi; Melissa J Kasiewicz; Annah S Rolig; Nisha Holay; Bryan Becklund; Anya Polovina; Sae Jeong Ahn; Brendan P Eckelman; Rashi Yadav; Thi Staebler; Noah D Simons; et al. (Journal for ImmunoTherapy of Cancer)
Background Immunotherapies targeting immune checkpoint inhibitors have revolutionized cancer treatment but are limited by incomplete patient responses. Costimulatory agonists like OX40 (CD134), a tumor necrosis factor receptor family member critical for T-cell survival and differentiation, have shown preclinical promise but limited clinical success due to suboptimal receptor activation. Conventional bivalent OX40 agonists fail to induce the trimeric engagement required for optimal downstream signaling. To address this, we developed INBRX-106, a hexavalent OX40 agonist designed to enhance receptor clustering independently of Fc-mediated crosslinking and boost antitumor T-cell responses.Methods We assessed INBRX-106’s effects on receptor clustering, signal transduction, and T-cell activation using NF-kß reporter assays, confocal microscopy, flow cytometry, and single-cell RNA sequencing. Therapeutic efficacy was evaluated in murine tumor models and ex vivo human samples. Clinical samples from a phase I/II trial (NCT04198766) were also analyzed for immune activation.Results INBRX-106 demonstrated superior receptor clustering and downstream signaling compared with bivalent agonists, leading to robust T-cell activation and proliferation. In murine models, hexavalent OX40 agonism resulted in significant tumor regression, enhanced survival, and increased CD8+ T-cell effector function. Clinical pharmacodynamic analysis in blood samples from patients treated with INBRX-106 showed heightened T-cell activation and proliferation, particularly in central and effector memory subsets, validating our preclinical findings.Conclusions Our data establish hexavalent INBRX-106 as a differentiated and more potent OX40 agonist, showcasing its ability to overcome the limitations of conventional bivalent therapies by inducing superior receptor clustering and multimeric engagement. This unique clustering mechanism amplifies OX40 signaling, driving robust T-cell activation, proliferation, and effector function in preclinical and clinical settings. These findings highlight the therapeutic potential of INBRX-106 and its capacity to redefine OX40-targeted immunotherapy, providing a compelling rationale for its further clinical development in combination with checkpoint inhibitors.